Imaging and serum analysis of immune complex formation of radiolabelled infliximab and anti-infliximab in responders and non-responders to therapy for rheumatoid arthritis. Issue 2 (22nd June 2006) - van der Laken, C J; Voskuyl, A E; Roos, J C; Stigter van Walsum, M; de Groot, E R; Wolbink, G; Dijkmans, B A C; Aarden, L A
Abstract : Background: Many patients with rheumatoid arthritis are currently successfully treated with infliximab (anti-tumour necrosis factor); however, about 30% of the patients do not respond to infliximab. One of the postulated hypotheses of not responding is the fast clearance of infliximab due to the development of infliximab–anti-infliximab complexes. Objective: To investigate the in vivo mechanism of not responding and the role of human anti-chimeric antibodies (HACAs) by using radiolabelled infliximab. Methods: Two responding and two non-responding patients with rheumatoid arthritis, infused with radiolabelled infliximab, were investigated by both imaging and serum analysis. Results: Images showed predominant presence of infliximab in blood up to 24 h, with a trend of faster blood clearance and of higher liver/spleen uptake in a non-responding patient. Clinically inflamed joints showed uptake of the drug. The HACA level in the non-responders was high (1641 and 1008 U/ml), but low or not detectable in responders. Sucrose gradients of serum showed antibody complexes in both non-responders. Various sizes of antibody complexes, including very large ones, were observed in a non-responder who developed a serious infusion reaction. Conclusion: Formation of infliximab–anti-infliximab complexes were found in non-responders due to the presence of large amounts of HACA. This finding, supported by both imaging and serum analysis data, may explain failure of infliximab treatment.